Peran Mamah Muda Sebagai Konselor Sebaya Dalam Upaya Degradasi Stunting Di Ponorogo (Indonesian Journal of Learning Education and Counseling, 2019)
This study aims to determine the role of young mama in the effort to stunting degradation in ponorogo. This research was using quantitative descriptive methods. The population of this study was all young mama in Krebet village while the sample of this study was BKB cadres in Krebet village. The sampling technique used is using stratified random sampling technique.The results showed that an increase of 23% was related to understanding of stunting. If seen in each indicator of understanding stunting also experienced an increase. The young mama community has an important role in efforts to stunting degradation. Especially in an effort to establish friendships, share information and share problems experienced